COVID-19 and Psychological Distress in Africa Communitarian Perspectives - Ndasauka, Yamikani (Routledge Research in Psychology, 2024)
This timely book draws on unique African experiences to explore the intersection between mental health and African communitarianism in the context of COVID-19, giving voice to the perspectives of vulnerable populations facing pre-existing challenges such as depression, anxiety, and stress. Advancing knowledge and contributing to the global debate about the effects of the pandemic on the psychological well-being of African people, chapters critique the role of media, information, misinformation, and disinformation during this period on individual- and community-based mental health. Using a holistic approach, the book highlights the need to prioritise the localising of mental health systems and clinical services to provide a better standard of care and comprehensive, context-specific mental health interventions that consider the heterogeneity within and between African regions. The book demonstrates through nuanced evidence and analysis that communitarian perspectives allow African societies to balance collective solidarity with individual well-being to benefit overall mental health. Ultimately drawing on communal values and localised knowledge to cultivate resilience to fight the psychosocial impacts of COVID-19 in Africa, the book will be of interest to scholars, postgraduate students and researchers exploring psychology, philosophy of mental health, and public health policy more broadly, as well as and cultural studies and the sociology of pandemics.